(untitled) (Research, Society and Development, 2022)
The combination of the fundamental laws of thermodynamics results in exergy, a size that quantitatively represents the ability to do useful work. Whenever energy is used, in processes where energy is converted into useful work, some of it is lost. The exergetic efficiency is a useful factor of rationality for the consumption and waste of systems. Several authors highlight the importance of exergetic analysis in different aspects of life, and it can be applied to the human body to assess the quality of energy conversion processes in biological systems, as well as in the biochemical processes of metabolism. The objective of the present article is to carry out an integrative review of the literature on the relationship between exergy analysis and the processes associated with the systems of the human body. The research developed over the years has shown a growing interest in the subject and presents an important improvement of the mathematical models of exergetic analysis, contributing to a better understanding of the performance of the human body and its systems from the laws and concepts of thermodynamics. In addition, future perspectives are created for the use of exergetic performance to aid in the field of medicine.